Gender differences in suicidal behavior in adolescents and young adults: systematic review and meta-analysis of longitudinal studies - Miranda-Mendizabal, Andrea; Castellví, Pere; Parés-Badell, Oleguer; Alayo, Itxaso; Almenara, José; Alonso, Iciar; Blasco, Maria Jesús; Cebrià, Annabel; Gabilondo, Andrea; Gili, Margalida; Lagares, Carolina; Piqueras, José Antonio; et al. (International journal of public health, 2019)
Objectives To assess the association between gender and suicide attempt/death and identify gender-specific risk/protective factors in adolescents/young adults. Methods Systematic review (5 databases until January 2017). Population-based longitudinal studies considering non-clinical populations, aged 12–26 years, assessing associations between gender and suicide attempts/death, or evaluating their gender risk/protective factors, were included. Random effect meta-analyses were performed. Results Sixty-seven studies were included. Females presented higher risk of suicide attempt (OR 1.96, 95% CI 1.54–2.50), and males for suicide death (HR 2.50, 95% CI 1.8–3.6). Common risk factors of suicidal behaviors for both genders are previous mental or substance abuse disorder and exposure to interpersonal violence. Female-specific risk factors for suicide attempts are eating disorder, posttraumatic stress disorder, bipolar disorder, being victim of dating violence, depressive symptoms, interpersonal problems and previous abortion. Male-specific risk factors for suicide attempt are disruptive behavior/conduct problems, hopelessness, parental separation/divorce, friend’s suicidal behavior, and access to means. Male-specific risk factors for suicide death are drug abuse, externalizing disorders, and access to means. For females, no risk factors for suicide death were studied. Conclusions More evidence about female-specific risk/protective factors of suicide death, for adolescent/young adults, is needed.